A Study on the Battery Recycling Process and Risk Estimation - Kim, Taeho; Yoon, Cheolhee; Jung, Seungho (International Journal of Environmental Research and Public Health, 2024)
The demand for the use of secondary batteries is increasing rapidly worldwide in order to solve global warming and achieve carbon neutrality. Major minerals used to produce cathode materials, which are key raw materials for secondary batteries, are treated as conflict minerals due to their limited reserves, and accordingly, research on the battery recycling industry is urgent for the sustainable secondary battery industry. There is a significant risk of accidents because there is a lack of prior research data on the battery recycling process and various chemicals are used in the entire recycling process. Therefore, for the safety management of related industries, it is necessary to clearly grasp the battery recycling process and to estimate the risk accordingly. In this study, the process was generalized using the information on the battery recycling process suggested in the preceding literature. And to estimate the relative risk of each battery recycling process, the RAC (Risk Assessment Code) matrix described in the US Department of Defense’s “MIL-STD-882E” was used. Severity was derived by using “NFPA 704”, and probability was derived by combining generalized event analysis for each process and the WEEE (Waste Electrical and Electronic Equipment) report. The results confirmed that the process using H2SO4 had the highest risk when extracting Li during the leaching process, and that dismantling and heat treatment had the lowest risk. Using the probability factor for each process calculated through the research, it is expected to be used in future battery recycling process research as basic data for quantitative risk assessment of the battery recycling process.
Keywords: Electric Power Supplies; Recycling; Risk Assessment; battery; battery recycling; hydrometallurgical process; RAC matrix; risk assessment